Both Perimenopausal Vasomotor Symptoms and associated anxiety disorder be managed with Escitalopram : An experience at a tertiary care Hospital - Muhammad Mohsin Rana; Nauman Khalid; Asifa Alia; Qasim Rauf; Um-A-Aimen; Nadia Zulfiqar (Journal of University Medical & Dental College, 2026)
BACKGROUND & OBJECTIVE:Perimenopausal vasomotor symptoms (VMS) are distressing and often trigger mood disorders. Selective Serotonin Reuptake Inhibitors (SSRIs) may improve both. This study evaluated the incidence and severity of anxiety in menopausal women with VMS and assessed the efficacy of Escitalopram in managing both conditions.METHODOLOGY:An interventional, multicenter, observational study was conducted from January to July 2023 at Rai Medical College, Sargodha, and private clinics. Women aged 30–75 years with VMS (per STRAW staging) and anxiety were included. Exclusions were HRT, prior SSRIs/NSRIs, hypersensitivity, certain neurological/psychiatric disorders, malignancy, and major systemic diseases. The Vasomotor domain of the MENQOL questionnaire was used for the Composite Symptoms Severity Index (CSSI), and anxiety was measured using the GAD-7 scale. Patients with GAD >4 or CSSI >50 received Escitalopram 10 mg daily. Scores were reassessed at 8 and 12 weeks. Data were analyzed using SPSS 25, chi-square, and Fisher’s exact test.RESULTS:A total of 346 patients were enrolled in the study. Baseline anxiety (minimal, mild, moderate, severe) varied across CSSI groups. By week 12, the proportion with minimal anxiety increased markedly (e.g., from 36% to 75% in one group), while moderate and severe anxiety declined across all groups. CSSI scores also showed consistent improvement from 8 to 12 weeks.CONCLUSION:Escitalopram significantly reduced both anxiety and vasomotor symptom severity in perimenopausal women, with improvements evident by week 8 and sustained through week 12.